2019
DOI: 10.1002/adfm.201808188
|View full text |Cite
|
Sign up to set email alerts
|

Organic Transistor Based on Cyclopentadithiophene‐Benzothiadiazole Donor–Acceptor Copolymer for the Detection and Discrimination between Multiple Structural Isomers

Abstract: Distinguishing structural isomers is a critical and challenging task for biotechnology, chemical industry, and environmental monitoring. Approaches currently available are limited in terms of selectivity and simplicity. In this paper, a highly sensitive organic field-effect transistor (OFET) using the cyclopentadithiophene-benzothiadiazole (CDT-BTZ) copolymers as a semiconductor is presented for easy and selective detection of different families of structural isomers, as well as between different isomers withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…Over the past decades, organic field‐effect transistors (OFETs) have received considerable attentions owing to their great potential applications in next‐generation flexible and low‐cost electronics, such as displays, [ 1–4 ] artificial skin, [ 5–7 ] chemical sensors, [ 8–10 ] etc. OFETs are composed of source/drain electrodes, gate electrode, dielectric layer and organic semiconductor layer.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, organic field‐effect transistors (OFETs) have received considerable attentions owing to their great potential applications in next‐generation flexible and low‐cost electronics, such as displays, [ 1–4 ] artificial skin, [ 5–7 ] chemical sensors, [ 8–10 ] etc. OFETs are composed of source/drain electrodes, gate electrode, dielectric layer and organic semiconductor layer.…”
Section: Introductionmentioning
confidence: 99%
“…OFET devices are generally fabricated using conventional metal oxide (e.g., SiO 2 ) gate insulators, as these have been used as a platform to study the effect of OSC molecular design and film structure on the sensitivity, selectivity, and stability of the sensing performance of OFETs 6–8. However, these materials are brittle in nature and typically require high processing temperatures that are unsuitable for fabrication on flexible plastic substrates.…”
mentioning
confidence: 99%
“…Another sensor based on cyclopentadithiophene-benzothiadiazole (CDT-BTZ) copolymer also distinguished the structural isomer of VOCs (p-xylene, m-xylene, o-xylene, Hexanal, 2-Hexanone, Heptanal, 3-Heptanone) (Figure 9C-E). 86 A single sensing parameter from transfer curve of OFET could identify the VOCs over a range of concentrations. Katz et al reported an OFET-based nerve agent simulant dimethyl methylphosphonate (DMMP) sensor by using bi-layer structure.…”
Section: Other Sensors In Gas Phasementioning
confidence: 99%